2009
DOI: 10.4102/sajp.v65i2.80
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercising with manual compression foot pumps, on dialysis efficiency, in patients with end stage renal disease

Abstract: Aim: This study aimed to establish if exercising with manual compressionfoot-pumps, could be used as an intervention to improve dialysis efficacy. A  pre test -post test design was used to test the intervention. Subjects were invited to participate in the study depending on whether they fitted the eligibility criteria of the study. Eight weeks after entry into the study pre-test values of dialysis efficacy (Kt/V ) were established prior to the implementation of an eight-week exercise programme followed by the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 10 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Seven of the 13 studies that reported spKt/V urea showed no statistical significance and small effect sizes for intradialytic exercise . Six of the 13 studies that reported spKt/V urea favored intradialytic exercise showing statistical significance and/or a large effect size. Only three studies reported eKt/V urea , all of which showed intradialytic exercise to have no effect.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Seven of the 13 studies that reported spKt/V urea showed no statistical significance and small effect sizes for intradialytic exercise . Six of the 13 studies that reported spKt/V urea favored intradialytic exercise showing statistical significance and/or a large effect size. Only three studies reported eKt/V urea , all of which showed intradialytic exercise to have no effect.…”
Section: Resultsmentioning
confidence: 96%
“…A total of 15 studies were included in the review (Figure ; Table ). Eight studies investigated the effects of an acute bout of exercise on dialysis adequacy, whilst seven studies performed a chronic intradialytic intervention . Seven of the acute studies utilized a within‐subject crossover design, with six of the seven randomizing the treatment order.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations